2019
DOI: 10.15640/jibe.v7n2a12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ESG Performance on Economic Performance in the High Profile Industry in Indonesia

Abstract: This study aims to examine the effects of ESG performance on economic performance. This research was conducted in 2015-2017 and produced 387 samples. The analysis technique used is multiple regression analysis with SPSS Statistics program 23. The results of the study show that ESG performance has a positive effect on economic performance. In further analysis, environmental performance and social performance shows that there is no influence on economic performance, except environmental performance which negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
(68 reference statements)
2
17
2
Order By: Relevance
“…The large number of stakeholders who care about ESG issues in business makes this contextual issue interesting to study. Previous research on the impact of ESG on firm performance has shown inconsistent results (Yawika & Handayani, 2019;Li et al, 2021). The research result of Duque-Grisales & Aguilera-Caracuel (2021) shows that the relationship between ESG scores and financial performance is statistically negative.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The large number of stakeholders who care about ESG issues in business makes this contextual issue interesting to study. Previous research on the impact of ESG on firm performance has shown inconsistent results (Yawika & Handayani, 2019;Li et al, 2021). The research result of Duque-Grisales & Aguilera-Caracuel (2021) shows that the relationship between ESG scores and financial performance is statistically negative.…”
Section: Introductionmentioning
confidence: 91%
“…Information about a company's ESG can generally be obtained through sustainability report, annual report, financial report, company website, external data provider agencies and other sources (Yawika & Handayani 2019;Manita, Bruna, Dang, & Houanti 2018). This report can reduce information asymmetry and ensure honest signals to different stakeholder (Bae, Masud, & Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Melnyk et al [32] thus argue that the value of firms can be increased and that new investors can be attracted by improving firms' environmental performance. In effect, strong environmental activities help firms avoid any business influences as a result of pollution problems, which will result in saving costs [33].…”
Section: Corporate Environmental Sustainability Practices and Firm Valuementioning
confidence: 99%
“…Thus, firms will have superior opportunities in the market if they have the confidence and support of society. These opportunities can increase the ability for a firm to produce value [33]. In addition, for a firm to acquire legitimacy in its operations and decrease the risks that it might face, the firm needs to reveal information with enhanced quality [68].…”
Section: The Relationship Between Corporate Environmental Sustainability Disclosure and Firm Valuementioning
confidence: 99%
“…The market structure of the star hotel can also be analysed using HHI, which is the sum of the squares of the market share of each star hotel. According to Khan and Hanif (2018) and Yawika and Handayani (2019), the value of this index is between more than 0 to 1. If the index is close to 0, it means that the industrial structure tends to be perfect market competition, while if the index is close to 1, it tends to be monopolistic.…”
Section: Herfindahl-hirschman Indexmentioning
confidence: 99%